Unveiling the Power of Educational Mathematics Applications as Formative Assessment Tools: A Multiple Case Study - Luzano, Jay Fie Paler; G. Nallada, Jayson; Russ B. Hulagpos, Daniel; John Rey C. Damasco, John (Universitas Terbuka, 2024)
This study explored the experiences of the second-year students of Bukidnon State University on their utilization of Symbolab and Photomath applications as formative assessment tools in their calculus studies. This study utilized the data source triangulation method in collecting data based on interviews, observation of interaction, and document analysis (Carter, Bryant-Lukosius, DiCenso, Blythe & Neville, 2014). The data were collected through face-to-face and virtual interviews using a semi-structured interview guide. Thematic analysis was utilized for data analysis. Findings revealed four (4) themes: (1) Learning Support in Mathematics, (2) Ethical Use of Math Applications, (3) User-Friendly Math Application Features, and (4) Accessibility and Inclusivity of Math Applications. This study recommends that students and teachers are urged to actively utilize these two (2) applications to enrich their learning experiences and expertise in calculus respectively.